Formação profissional e desenvolvimento local: relações e oportunidades a partir da elaboração do projeto educativo de um município português - ALCOFORADO, Joaquim Luís Medeiros (Universidade Federal do Pará, 2021)
By combining professional training policies with technological innovations, changes in production and work organization seek to define strategies that result in the individual’s effective participation in their production environment. With an integrative intention and by taking into account the processes and contexts’ changes of the economy sectors, professional training entities should, by adopting a broader view of action, focus on the development of training initiatives adjusted to society’s real needs and, specially, adjusted to the local community in which the citizens act. As a result, within a municipal context’s education strategic project – Local Educational Project – developed between the University of Coimbra and a Lisbon’s Metropolitan Area County (Sintra), still in a diagnostic phase and by using the Focus Group technique, some companies and training institutions representatives of the territory counties were heard about the business characterization and its needs in terms of human resources and training areas. Assuming that local development calls for the participation of all agents and all people, based on a holistic preparation, professional education, as a vital contribution to economic, social and cultural development, becomes a multidimensional phenomenon essentially focused on promoting action capacities and strengthening the conditions for individual and group participation, in the processes of integrated and sustained development, based on the realities of people and their communities.